COVID-19 infection, inception and immunity: Observations and recommendations in the light of vitamin D? - Vivek Dixit; Bhavuk Garg; Nishank Mehta; James Pegrum; Dinesh Dhanwal (Elsevier, 2021)
Responsive immunity plays an important role fighting against infections. Worldwide, Vitamin D deficiency is a major concern not only for musculoskeletal health but also affecting the immunity status in population. Amidst COVID-19 pandemic, it is imperative to establish the role of vitamin D in destruction of pathogens. Vitamin D awareness program at school level might be an effective health governance policy to educate populations for the importance of vitamin D in overall health.